Ascension and ecclesia : on the significance of the doctrine of the Ascension for ecclesiology and Christian cosmology /: on the significance of the doctrine of the Ascension for ecclesiology and Christian cosmology. (1999) - Farrow, Douglas, 1953-
No abstract available